Reflexión sobre el obstáculo epistemológico del concepto de medición en contabilidad - Habdelgani Hachim, Nasser; Lemos de la Cruz, Jorge Eduardo (Libre Empresa, 2010)
When it is said that accounting measures or conducts measurements, one repeatedly comes across the use of concepts such as value, price, money, salary, and goods as part of the statement of measurement in accounting. A review of these concepts will make it possible to establish that the value theory proposed by classic economics contributes meanings that do have a metric conceptual concept. Yet, not all of these meanings can be applied to measurements. This article is aimed at providing a conceptual clarification of the use of these basic concepts in some statements in accounting terminology that relate to the explicit statement of accounting measurement. It reviews some of the most representative authors of accounting books, such as Eldon Hendriksen and José María Requena, and thus analyzes the epistemological obstacle of the notion of measurement in accounting. This article is a conceptual critical reflection that arises from a research project titled “The notion of accounting measurement” by the “Accounting Alternatives” research team at Libre University.